2016
DOI: 10.1016/j.jid.2016.06.618
|View full text |Cite
|
Sign up to set email alerts
|

AP1S3 Mutations Cause Skin Autoinflammation by Disrupting Keratinocyte Autophagy and Up-Regulating IL-36 Production

Abstract: Prominent skin involvement is a defining characteristic of autoinflammatory disorders caused by abnormal IL-1 signaling. However, the pathways and cell types that drive cutaneous autoinflammatory features remain poorly understood. We sought to address this issue by investigating the pathogenesis of pustular psoriasis, a model of autoinflammatory disorders with predominant cutaneous manifestations. We specifically characterized the impact of mutations affecting AP1S3, a disease gene previously identified by our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
145
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(149 citation statements)
references
References 25 publications
2
145
0
2
Order By: Relevance
“…In addition, AP1S3 knockdown disrupts keratinocyte autophagy, causing abnormal accumulation of p62, an adaptor protein mediating NF‐κB activation. As a consequence, AP1S3 ‐deficient cells upregulated IL‐1 signaling and overexpress IL‐36α . All together, these results indicate that IL‐36 may play an important role in psoriasis as well as in other inflammatory skin pathologies (Figure ).…”
Section: Il‐36 In Skinmentioning
confidence: 68%
“…In addition, AP1S3 knockdown disrupts keratinocyte autophagy, causing abnormal accumulation of p62, an adaptor protein mediating NF‐κB activation. As a consequence, AP1S3 ‐deficient cells upregulated IL‐1 signaling and overexpress IL‐36α . All together, these results indicate that IL‐36 may play an important role in psoriasis as well as in other inflammatory skin pathologies (Figure ).…”
Section: Il‐36 In Skinmentioning
confidence: 68%
“…Autophagy negatively regulates TLR2/6 mediated NF-κB activation, SQSTM1 expression, and cytokine secretion in human keratinocytes that are critical to skin inflammation as observed in psoriasis/psoriatic arthritis [54]. Indeed other studies have shown that mutation of psoriasis risk gene AP1S3 that leads to impaired autophagy, and accumulation of SQSTM1, results in up-regulation of IL-36 in keratinocytes and causes skin inflammation [84]. Furthermore, increased expression of autophagy-related protein ATG16L1 is observed in dendritic cells derived from psoriatic arthritis patients compared to healthy controls that suggests autophagy involvement in psoriatic arthritis pathogenesis [85].…”
Section: Autophagy/autophagy-related Proteins In Autoimmune Diseasesmentioning
confidence: 99%
“…Genetic variants in CARD14 have also been implicated as disease‐causing/disease‐contributing factors in patients with GPP and PPP; in vitro experiments of most of these variants suggest an activation of nuclear factor kappa B (NF‐κB) . Two missense variants in AP1S3 have further been described to contribute to ACH, GPP and PPP and in vitro analysis suggests a reduced protein function resulting in disruption of keratinocyte autophagy and an increased activation of NF‐κB leading to upregulation of IL‐1 signalling and overexpression of IL‐36α …”
mentioning
confidence: 99%